EVALUATION OF DIFFUSION-COEFFICIENTS IN OSMOTIC CONCENTRATION OF BANANAS (MUSA-CAVENDISH LAMBERT) - Mauro, M. A.; Menegalli, F. C. (Blackwell Science, 1995)
The effect of time of exposure, solution concentration and temperature on the osmotic concentration of banana (slices of 11 mm thickness) was studied in aqueous sucrose solutions. The selectivity of the cellular tissues was reduced by steam blanching the banana slices before osmotic treatment. Effective diffusion coefficients for the loss of water and the increase in sucrose content were determined according to Fick's Law applied to a two-dimensional body; calculated on the basis of the concentration of various components in the liquid phase impenetrating the fruit. These coefficients revealed values similar to binary diffusion coefficients for pure sucrose solutions.
Keywords: DEHYDRATION; Diffusion coefficient; FICKS LAW; FRUIT PRESERVATION; Sucrose